Evaluation of the Social Skill Levels of the Horseman Jereed Players with Respect to DiffrentVariables - Meriç Eraslan; Mustafa Baş; Seran Aka (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to evaluate the social skill levels of the horsemen jereed players in Turkey. 330 players from different cities in Turkey have attended to the research. Social Skills Inventory developed by Riggio in 1986 has been used to evaluate the social skill levels of the players. This inventory which is a self-identifying test tool consisting of 90 terms was translated in to Turkish by Galip Yüksel in 1993. Grade point averages, minimum and maximum grades, standard deviation and range values have been calculated as the identifying parameters to evaluate and analyze the data obtained from SBE and personal information forms collected from the players attending to study. Independent groups T test and analyses of variance (ANOVA) have been used to determine if the data provided in the forms like the age, education, life quality and marital status of the players have a considerable effect on their social skill levels. In conclusion, it is seen that jereed players have mid-level social skills both in general and sub-dimensions. Moreover, it has been concluded that the social skills levels of the ones who are single (p=0,005) , under 21(p=0,000- p=0,013- p=0,002) or over 42 (p=0,000- p=0,026), university graduate (p=0,000- p=0,000)  and living under good (p=0,001- p=0,000) to very good life standards (p=0,000- p=0,000 )  have better social skills levels than those who're married, over 21 or under 42, high school, junior or middle school graduate, living under bad to very bad life standards.